Evaluation Of Immunohistochemical Expression Of Her2/Neu In Prostate Adenocarcinoma - Santosh Kumar Sidhwani; Serajuddaula Syed; Faraz Ahmed Baig (ziauddin University, 2024)
Background: Prostate cancer is the second most common cancer in men. Diagnosis of prostate cancer mainly depends upon histological examination. Prostate cancer expresses various immune markers, for example HER2/neu. The objective of this study was to determine and score the immunohistochemical expression of HER2/neu in prostate adenocarcinoma biopsies. We have also compared the association of HER2/neu expression with biological behavior and risk factors of prostate adenocarcinoma. Methods: A cross sectional study was carried out using prostate biopsies, clinically suspected of prostate adenocarcinoma. The diagnosis of adenocarcinoma was confirmed and histological characterization was done by evaluating the morphological features. The tumors were graded according to the revised 2015 Gleason's grouping. Immunohistochemical analysis for HER2/neu expression was performed in the most representative tumor block. Mean frequency and percentages were calculated for quantitative variables, whereas chi-square test and Fisher's Exact Test were applied for qualitative variables. P-value of < 0.05 was considered as significant. Results: Only one case showed moderate HER2/neu expression. An insignificant statistical difference was observed between HER2/neu expression and prostate adenocarcinoma. The positive case had age more than 60 years with moderately increase in serum PSA levels and was aggressive in nature at the time of diagnosis. Conclusion: Our results indicated that HER2/neu expression is absent or very rare in prostate adenocarcinoma. Key Words: Prostate, adenocarcinoma, Gleason's Group, Serum PSA, HER2/neu Background: Prostate cancer is the second most common cancer in men. Diagnosis of prostate cancer mainly depends upon histological examination. Prostate cancer expresses various immune markers, for example HER2/neu. The objective of this study was to determine and score the immunohistochemical expression of HER2/neu in prostate adenocarcinoma biopsies. We have also compared the association of HER2/neu expression with biological behavior and risk factors of prostate adenocarcinoma. Methods: A cross sectional study was carried out using prostate biopsies, clinically suspected of prostate adenocarcinoma. The diagnosis of adenocarcinoma was confirmed and histological characterization was done by evaluating the morphological features. The tumors were graded according to the revised 2015 Gleason's grouping. Immunohistochemical analysis for HER2/neu expression was performed in the most representative tumor block. Mean frequency and percentages were calculated for quantitative variables, whereas chi-square test and Fisher's Exact Test were applied for qualitative variables. P-value of < 0.05 was considered as significant. Results: Only one case showed moderate HER2/neu expression. An insignificant statistical difference was observed between HER2/neu expression and prostate adenocarcinoma. The positive case had age more than 60 years with moderately increase in serum PSA levels and was aggressive in nature at the time of diagnosis. Conclusion: Our results indicated that HER2/neu expression is absent or very rare in prostate adenocarcinoma. Key Words: Prostate, adenocarcinoma, Gleason's Group, Serum PSA, HER2/neu